Cell and extracellular matrix growth theory and its implications for tumorigenesis. (March 2021) - Sauer, T.J.; Samei, E.; Bejan, A.
Abstract: Cells associated with an abnormal (cancerous) growth exchange flows, morph freely and grow hand-in-glove with their immediate environment, the extracellular matrix (ECM). The cell structure experiences two mass flows in counterflow. Flowing into the structure are nutrients and flowing out is refuse from the metabolically active biomass within. The physical effect of the evolution of the cell and extracellular structure is more flow and mixing in that space, that is, more mixing than in the absence of a biological growth in that space. The objective of the present theory is to predict the increase in the size of the cell cluster as a function of its structure, and also to predict the critical cluster sizes that mark the transitions from one distinct cluster configuration to the next. This amounts to predicting the timing and the main features of the transitions from single cell to clusters with two, four, eight and more cells, including larger clusters with cells organized on its outer surface. The predicted evolution of the size and configuration of the cell cluster is validated successfully by comparison with measurements from several independent studies of cancerous and non-cancerous growth patterns.